NEW APPROACHES TO THE STATISTICAL ANALYSIS OF THE RESULTS OF PEDAGOGICAL EXPERIMENT - Petruk , Vira; Semenikhina, Olena; Sabadosh, Yuliia (Physical and Mathematical Education, 2022)
Formulation of the problem. Scientific work related to statistical analysis of data is often oversaturated with mathematical formulas to justify the proposed approach, and therefore difficult to accept or even reject by social and humanitarian scientists. Therefore, such approaches to statistical verification of results are becoming relevant, which, on the one hand, are based on the correct mathematical apparatus, and on the other hand, simplify the perception of cumbersome empirical data and on a scientific basis allow qualitative conclusions.Materials And Methods. To achieve the result used: theoretical analysis of scientific sources to determine the theoretical foundations of statistical analysis in pedagogical research, comparative analysis, and comparison of results of scientific and pedagogical research to determine the most popular methods of statistical analysis; content analysis of Internet resources to determine resources for automation of statistical calculations; empirical methods (pedagogical experiment) to demonstrate the process of processing empirical data according to the developed methodology.Results. The author's approach to statistical analysis of the results of pedagogical experiments is based on two positions: 1) integrated consideration of changes in the means and variances of both samples: the idea is to simultaneously analyze samples by Student's and Fisher's criteria conclusion on the effectiveness of the author's model or approach; 2) tracking the intermediate results of the pedagogical experiment for timely adjustment of the developed methodology or approach: the idea is that the pair "control group and experimental group at the refinement stage of the experiment" is monitored first, the method is improved (or not), and the new pair "control group and experimental group at the formative stage of the experiment" author's method is finally confirmed.Conclusions. The proposed algorithm of statistical analysis of the results of the pedagogical experiment not only automates calculations but also has an advantage over other statistical methods in that the researcher can only analyze tabular pairs of averages and variances on the significance of differences and draw appropriate conclusions. We see the implementation of the algorithm in scientific and pedagogical practice as promising and the writing of a macro that automates the filling of the table based on the entered data of three samples.
Keywords: pedagogical experiment; statistical analysis of the results of pedagogical experiment; scientific and pedagogical research; comparison of means and variances; statistical analysis; experimental model; specialist training